2024
DOI: 10.1017/cts.2024.3
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of telemedicine applications in decentralized research

Mollie R. Cummins,
Hiral Soni,
Julia Ivanova
et al.

Abstract: Telemedicine enables critical human communication and interaction between researchers and participants in decentralized research studies. There is a need to better understand the overall scope of telemedicine applications in clinical research as the basis for further research. This narrative, nonsystematic review of the literature sought to review and discuss applications of telemedicine, in the form of synchronous videoconferencing, in clinical research. We searched PubMed to identify relevant literature publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Leveraging the acceptability of telemedicine for clinical care, a literature review by Cummins et al notes the power of this technology for clinical research and summarizes its many uses [ 12 ]. In another study reported in this issue, Cummins et al describe the breadth of technologies now being incorporated into clinical research to support decentralization, including centralized regulatory management, electronic signatures and consent, online payment systems, electronically delivered patient-reported outcome measures, wearables, and even home health nursing portals [ 13 ].…”
Section: Innovations and Deployment At Scalementioning
confidence: 99%
“…Leveraging the acceptability of telemedicine for clinical care, a literature review by Cummins et al notes the power of this technology for clinical research and summarizes its many uses [ 12 ]. In another study reported in this issue, Cummins et al describe the breadth of technologies now being incorporated into clinical research to support decentralization, including centralized regulatory management, electronic signatures and consent, online payment systems, electronically delivered patient-reported outcome measures, wearables, and even home health nursing portals [ 13 ].…”
Section: Innovations and Deployment At Scalementioning
confidence: 99%